2001
DOI: 10.1097/00002030-200101050-00011
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz plasma levels can predict treatment failure and central nervous system side effects in HIV-1-infected patients

Abstract: Treatment failure and CNS side-effects are associated with low and high efavirenz plasma levels, respectively. The important inter-individual variability in efavirenz levels strongly argues for dose adjustment on the basis of therapeutic drug monitoring to optimize treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
449
10
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(498 citation statements)
references
References 8 publications
24
449
10
4
Order By: Relevance
“…Due to impracticalities in obtaining brain tissue from patients, some groups have used concentrations in cerebrospinal fluid (CSF) as a surrogate for brain concentrations. The majority of pharmacokinetic (PK) studies have focused on describing efavirenz plasma concentrations and elucidating genetic factors that contribute to the variability in efavirenz PK or genetic associations to predict patients at risk of developing CNS toxicity (1,7,8). However, a few small studies investigated efavirenz PK in both plasma and CSF.…”
mentioning
confidence: 99%
“…Due to impracticalities in obtaining brain tissue from patients, some groups have used concentrations in cerebrospinal fluid (CSF) as a surrogate for brain concentrations. The majority of pharmacokinetic (PK) studies have focused on describing efavirenz plasma concentrations and elucidating genetic factors that contribute to the variability in efavirenz PK or genetic associations to predict patients at risk of developing CNS toxicity (1,7,8). However, a few small studies investigated efavirenz PK in both plasma and CSF.…”
mentioning
confidence: 99%
“…[12] Many studies have looked at the effect of the EFV drug level on the frequency of side-effects. Marzolini et al [10] reported a 24% increase in CNS side-effects if the plasma level was >4 000 ng/mL. However, other researchers have found no correlation between adverse effects and plasma concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…[7] CNS symptoms are the most frequently reported side-effects in HIVpositive patients on EFV, and include dizziness, headache, confusion, stupor, impaired concentration, agitation, amnesia, depersonalisation, hallucinations, insomnia and strange dreams. [6,[8][9][10][11][12][13][14] The frequency of CNS side-effects is estimated to be 20 -40%. [10] The majority of patients who develop CNS and psychiatric adverse effects do so in the first 6 weeks of treatment, [11] with most symptoms resolving by 6 -10 weeks after treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marzolini and co-workers proposed a 1000-4000 g/L plasma range at mid-dosing interval as a suitable target for EFV drug levels [2]. When EFV levels reach toxic levels (>4000 g/L) a higher incidence of side-effects occurs such as insomnia, dizziness, abnormal dreams and loss of concentration [2,3], while subtherapeutic levels (<1000 g/L) can lead to treatment failure due to viral resistance [4,5].…”
Section: Introductionmentioning
confidence: 99%